1992
DOI: 10.1136/bmj.304.6837.1276
|View full text |Cite
|
Sign up to set email alerts
|

Is Helicobacter pylori the cause of dyspepsia?

Abstract: Objective-To determine the association between infection with Helicobacterpylori and dyspepsia.Design-Cross sectional study of dyspeptic subjects and age and sex matched controls identified by a questionnaire survey of ali inhabitants aged 20-69. (Endoscopy, histological examination, and microbiological examinations of biopsies from the gastric mucosa were performed blind.)Setting-Population based survey in S0rreisa, Norway.Subjects-All 782 dyspeptic subjects (excluding those with a previous history of peptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
2
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(38 citation statements)
references
References 28 publications
3
30
2
3
Order By: Relevance
“…Bernersen et al found similar results and, in this study, a random population sample was endoscoped whether or not they had symptoms 29 .…”
Section: Role Of H Pylori In Dyspepsia and Non-ulcer-dyspepsiasupporting
confidence: 62%
“…Bernersen et al found similar results and, in this study, a random population sample was endoscoped whether or not they had symptoms 29 .…”
Section: Role Of H Pylori In Dyspepsia and Non-ulcer-dyspepsiasupporting
confidence: 62%
“…Non-ulcer dyspepsia had a significantly lower prevalence of H. pylori infection (53.1%) when compared with ulcer dyspepsia (83-88%). This would be supported by studies showing no correlation with infection in such patients 4,[15][16][17] . Eradication of H. pylori was however associated with a small but significant benefit, with treatment of 14 patients needed to cure one case of NUD 18 .…”
supporting
confidence: 66%
“…Acredita-se que mais de um terço dos carcinomas gástri-cos seja atribuído à infecção pelo H. pylori. 26,33,73,100 Outras afecções associadas à infecção pelo H. pylori são linfoma de tecido linfóide associado à mucosa gástrica -MALToma, 105 dispepsia não-ulcerativa, 10,12 doenças coronarianas e cardiovasculares, 90,108,98,107 urticária idiopática crônica, 29,110,129 doenças auto-imunes (púrpura de Henoch-Shönlein, 77,111 trombocitopenia auto-imune, 43 síndrome de Sjögren 37 ) e enxaqueca. 42 Estudos sugerem que existe aumento na incidên-cia de refluxo gastroesofágico (RGE) após erradicação do H. pylori da mucosa gástrica.…”
Section: Introductionunclassified